FINANCIAL TECHNOLOGY SEBAGAI SOLUSI DAN RESOLUSI NEW NORMAL PADA INDUSTRI JASA KEUANGAN - Alfonsa Dian Sumarna (Universitas Amikom Purwokerto, 2022)
Changes due to the Covid-19 pandemic have led to the emergence of new financial service types. Financial sector’s adoption using the Artificial Intelligence (AI) and Machine Learning (ML) is the key factor to survive, rise and grow. Today mostly people are familiar using technology in all side of life which causes a new normal needed to get convenience in all respects including on financial services. The financial services industry is increasingly using financial technology and new innovations in carrying out its functions and implementing new solutions that fundamentally intend to attract consumers. The purpose of this study is to examine and analysis changes in fintech adoption in the financial industry. This qualitative research using Secondary Data Analysis (SDA) which is describes the changes and impacts of the application of fintech on the financial industry from various perspectives of international surveys. The harmonization and adoption of fintech in the financial industry will bring changes to organizational governance and regulations. Organizational governance requires commitment and full support from management to triumph of fintech. The regulation will protect the rights of customers and also company itself from fraud that can be caused by fintech.